Marine lobsters of the world An annotated illustrated catalogue of species of interest to fisheries known to date. - Holthuis,L. B. (Rome, Italy FAO, 1991)
FAO fisheries synopsis ; no. 125FAO species catalogue ; v. 13
Keywords: Lobster fisheries; Lobsters